Improving quality of care in maternal, newborn and child health: opportunities and challenges for India - Jayanna, K (Indian Journal of Community Health, 2013)
Each year, more than 500000 mothers and nearly 4 million newborns die across the world due to causes related to pregnancy and child birth. 95% of these deaths occur in African and Asian countries (1). Deaths of newborns within the first 28 days contribute to 40% of all the under five deaths and a further three-fourth of the neonatal deaths occur within the first seven days after birth. While there has been considerable progress in the reduction of child deaths (13.2 million in 1990 to 9.2 million in 2007), the pace of reduction of maternal deaths has been slower (1). The causes of deaths are well known; effective preventive and curative interventions are available to address the causes of maternal, newborn and child deaths. While the countries are scaling up interventions, the lack of adequate focus on the quality of these interventions may affect the achievement of millennium development goals (MDG) 4 and 5 targets for children and mothers respectively (2). However, there have been attempts in the recent past to develop and study the feasibility of newer quality improvement tools and processes, especially in the context of developing countries (2). Audits have offered promise in this regard particularly, standards/criterion based audits (2). Developing a culture of quality within facilities and healthcare systems through the establishment of quality improvement teams and through identified champions is an important requisite for sustaining the focus on quality (3).